Using Spiral Scan Technique for Medical Image Watermarking with Tamper Detection and Recovery - Afifah Nailah, Muhamad; Jasni, Mohamad Zain (2007)
This paper will study the spiral scan technique for Medical Image Watermarking with Tamper Detection and Recovery by Jasni Mohd Zain (2006).The spiral algorithm in clockwise and anti-clockwise direction is presented to test when the tamper is made near to the centre of image. For ultrasound image, this is highly likely because the region of interest (ROI) happens to be in the centre of the image. Using spiral technique, we show that the block spiraling and starting in the middle will have a greater chance of recovery compared to the simple raster scan technique which is start from left to right starting at the top-left corner and reverse raster scan technique. Besides, we present the recovery rate of spiral scan technique in 6 X 6 block size of image with 2 X 2 and 4 X 4 block tamper. Recommendations will then be made to enhance the technique especially in the aspect of recovery or reconstruction rate for medical images.